DAMPAK PENGGUNAAN SMARTPHONE TERHADAP MOTIVASI EKSTRINSIK BELAJAR SISWA DI MI HIDAYATUL IHSAN DAN MI NURUL ISLAM KUALA TUNGKAL - M. Iriyansyah; Fitriyani Kosasih; Eliva Sukma Cipta (STKIP Subang, 2026)
The rapid advancement of digital technology has significantly influenced various aspects of education, particularly through the widespread use of smartphones among elementary school students. While smartphones offer valuable opportunities to support learning activities, their excessive and inappropriate use may negatively affect students' learning motivation. This study aimed to examine the impact of smartphone use on students' extrinsic learning motivation at MI Hidayatul Ihsan and MI Nurul Islam Kuala Tungkal. The study employed a quantitative approach with an ex post facto research design. The population consisted of fourth-, fifth-, and sixth-grade students from both Islamic elementary schools, with a sample of 98 respondents selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics version 26. The findings revealed that the level of smartphone use among students was categorized as high, whereas their extrinsic learning motivation was at a moderate level. The regression analysis indicated that smartphone use had a statistically significant effect on students' extrinsic learning motivation (p < 0.05), with a coefficient of determination (R²) of 0.318, indicating that smartphone use contributed 31.8% to the variance in students' extrinsic learning motivation. The study concludes that the educational impact of smartphone use depends largely on its purpose and intensity. Therefore, collaboration among schools, teachers, and parents is essential to encourage the productive use of smartphones as learning tools that enhance students' motivation and academic engagement.